“Okara” a New Preparation of Food Material with Antioxidant Activity and Dietary Fiber from Soybean - Suruga, Kohei; Kato, Akihisa; Kadokura, Kazunari; Hiruma, Wataru; Sekino, Yoshihiro; Buffington, C. A. Tony; Komatsu, Yasuhiho (IntechOpen, 2011)
None